The use of the marketing mix in tourism - Євтушенко, Олена (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The article is devoted to problems of implementation and use of marketing principles in business tourism market. The existing system of marketing tools, and limits its use in the tourism business and identifies and analyzes the factors that influence the tourism market in Ukraine. The article analyses the current state of marketing in the tourism industry and gives directions for its further development.